FACTORS THAT CONTRIBUTE TO THE SATISFACTION OF STUDENT IN THE MEDICAL RESIDENCY PROGRAM - Vitriana Biben; Dian Marta Sari; Farida Arisanti; Sunaryo B Sastradimadja (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: A high demand of physiatrist should be supported by quality assurance in education system of Physical Medicine & Rehabilitation (PMR) residency program, that could be done by evaluating satisfaction of its service users. This study was conducted to find the dimensions of service quality that influences the students satisfaction.Methods: A cross-sectional study with fifty subjects using total sampling technique was conducted. Service quality was evaluated using ServQual questionnaire consisted of five dimensions: ‘tangible’, ‘reliability’, ‘responsiveness’, ‘assurance’ and ‘empathy’. Statistical analysis consisted of bivariate analysis followed by a multivariate analysis was performed to determine the most significant dimension associated with student satisfaction which was measured using Likert scale.Results: Bivariate analysis revealed that all dimensions had significant association with satisfaction (p value < 0,05) except for ‘tangible’(p value = 0,060). Further multivariate analysis resulted in ‘reliability’ dimension as the most significant dimension associated with satisfaction (p value = 0,005; Adjusted OR = 142,67; CI 95% = 15,460-1316,587).Conclusion: Reliability is the most significant dimension associated with student satisfaction. Improvement of this dimension, followed by other significant dimensions would lead to satisfaction of the students.